Coconut Peeling System Berbasis PLC untuk Ekonomi Bangkit Pasca Pandemi - Hadi, Charis Fathul; Muliyono, Muliyono (Jurnal Arus Elektro Indonesia, 2023)
In the current post-pandemic era, the creativity of MSME actors is required so that the economy immediately rises, this is aimed at stabilizing the economic sector after almost 3 years of being hit by a pandemic. Increasing the level of creativity in sales must also be accompanied by an increase in the number of productions made, one of which is SMEs making fresh drinks from young coconuts. From the results of observations of SMEs in Banyuwangi district, especially in the business of making jelly. a young coconut seller can afford 16 seconds to two minutes at a time coconuts with the shape of one fruit and the other not being uniform. If within 10 minutes consumers come as many as 42 people or more to order young coconuts. So the peeling ability with the above time, is not comparable to the arrival of consumers, it makes consumers wait a long time and makes sellers want to peel quickly to meet consumer needs and will affect the shape of young coconuts that will be served to be unattractive. For this reason, a machine is designed that can help peel young coconut skin more quickly as a substitute for human labor, which in turn can increase the efficiency of young coconut peeler, both in terms of speed, power, production amount, to the safety factor of the peeler machine. So that consumer needs are met more quickly and more attractively to be presented. The methods used in this research are Phase 1 Needs Survey, Phase 2 Design, Phase 3 Prototype, Phase 4 Prototype Testing. From the test results, the frequency variation is 37 Hz, 44 Hz, 58 Hz. From the 3 variations found a frequency of 60 Hz which gets smooth and maximum stripping results.